Side Effects Experience on Behavior of Pregnant Women Consuming Iron Tablets - Istiana Intan; Munayarokh Munayarokh; Siti Rofi'ah (Midwifery and Nursing Research, 2020)
Background: Anemia was a disease that attracts worldwide concern and was a very big problem, especially in developing countries. The factor that caused high iron deficiency anemia in pregnant women was the low compliance of pregnant women in consuming iron tablets. Side effects in the form of nausea were the reason pregnant women did not comply with Iron tablets. The purpose of this study was to determine the relationship between the side effects experience and the behavior of pregnant women in consuming Iron tablets. This type of research was quantitative with analytic survey and using a cross sectional approach.Methods: This type of research was quantitative with analytic survey and using a cross sectional approach. The population in this study were pregnant women in the second and third trimesters in the working area of the Puskesmas Tempuran, Magelang Regency based on the February-March 2019 cohort, totaling 177 pregnant women with a sample of 123 pregnant women, calculated using the Slovin formula. The sampling technique used Proportionate Stratified Random Sampling. Data analysis used Kendall tau test.Results: The results showed that most of the pregnant women who consumed Iron tablets had side effects experience caused by the behavior of pregnant women in consuming Iron tablets, mostly in the low category.Conclusion: There was a relationship between the side effects experience and the behavior of pregnant women in consuming Iron tablets. It was recommended that pregnant women consume Iron tablets regularly in accordance with the recommendations of health workers so that they can prevent anemia.